The Defence of Duffer's Drift : A Few Experiences in Field Defence for Detached Posts Which May Prove Useful in Our Next War - Swenton, Ernest, Major General (Lahore, Pakistan Wajidali's Ltd., 1986)
This tale of a dream is dedicated to the "gilded Popinjays" and "hired assassins" of the British nation, especially those who are now knocking at the door, to wit the very junior. It embodies some recollections of things actually done and undone in South Africa, 1899-1902. It is hoped that its fantastic guise may really help to emphasise the necessity for the practical application of some very old principles, and assist to an appreciation of what may happen when they are not applied, even on small operations. This practical application has often been lost sight of in the stress of the moment, with dire results, quite unrealised until the horrible instant of actual experience. Should this tale, by arousing the imagination, assist to prevent in the future even one such case of disregard of principles, it will not have been written in vain. The dreams are not anticipations, but merely a record of petty experiences against one kind of enemy in one kind of country only, with certain deductions based thereupon. But from these, given the conditions, it is not difficult to deduce the variations suitable for other countries, or for those occasions when a different foe with different methods of fighting and different weapons has to be met
Keywords: South African War (1899-1902) -- Tactics -- Guerrilla warfare -- Military campaigns -- Military art and science